Glucagon-like peptide-2 induced hemodynamic alterations in the rat small intestine - (:unkn) unknown (My University, 2005)
Objective: Glucagon-like peptide-2 (GLP-2) is a 33 amino acid peptide produced in endocrine L-cells of the intestinal mucosa. The aim of the present study was to characterize whether GLP-2 alters the hemodynamic parameters of the small intestine and to find out possible mediators, Methods: After an overnight fasting, the rats were anesthetized with urethane. The right carotid artery and jugular vein were cannulated and a midline abdominal incision was made to isolate the superior mesenteric artery (SMA) for flow probe placement. GLP-2 at doses of 1, 5 and 10 μg/rat were infused into the jugular vein for 120 minute. SMA blood flow and resistance were measured and calculated. In an additional group, the animals were pretreated with atropine sulfate (1 mg/kg), teophylline (25 mg/kg) and ramosetron (100 μg/kg) given 20 minutes before the infusion of GLP-2 (5 μg/rat). Results: There was no significant difference in the mean arterial pressure of the untreated or GLP-2 treated rats throughout the experiments. GLP-2 administration at all doses increased the SMA blood flow compared with the untreated values. Neither atropine sulfate and ramosetron nor theophylline pretreatment significantly changed the blood flow responses obtained from GLP-2 infusion. Conclusion: These results demonstrated that GLP-2 induced changes in blood flow are not mediated by muscarinic, adenosine or serotonergic 5-HT3 receptors.
Keywords: Blood flow; GLP-2; Small intestine